2021
DOI: 10.1177/2325967121999643
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Repair of Distal Biceps Femoris Avulsion Injuries in Professional Athletes

Abstract: Background: Understanding the optimal management of distal biceps femoris avulsion injuries is critical for restoring preinjury function, restoring hamstring muscle strength, increasing range of motion, and minimizing risk of complications and recurrence. Due to the rarity of these injuries, prognosis and outcomes within the literature are limited to case reports and small case series. Purpose: To assess the effect of surgical repair for acute distal avulsion injuries of the biceps femoris tendon on (1) return… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 51 publications
0
14
0
5
Order By: Relevance
“…At 1-year follow-up, 91% were very satisfied with their outcomes, and there was no injury recurrence or need for secondary procedures. 3 Kayani et al reported on a series of 34 professional athletes who underwent suture repair of distal biceps femoris tears involving the myotendinous junction. 11 All athletes were able to return to preinjury level of sport at a mean of 11.7 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At 1-year follow-up, 91% were very satisfied with their outcomes, and there was no injury recurrence or need for secondary procedures. 3 Kayani et al reported on a series of 34 professional athletes who underwent suture repair of distal biceps femoris tears involving the myotendinous junction. 11 All athletes were able to return to preinjury level of sport at a mean of 11.7 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…8 Nonetheless, good clinical results have been reported with suture anchor repair of avulsion injuries, with return to preinjury level of sport seen in all 22 professional athletes in one case series. 3 However, intratendinous ruptures are exceedingly rare, with only one case described in a series of 18 distal hamstring ruptures by Lempainen et al 2 As such, information on management and outcomes following this type of injury is lacking.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MTJ injuries have been traditionally treated non-operatively with varying success in return to sport timing and recurrence of injury rates. There is evidence that surgical repair in proximal and distal high-grade MTJ injuries can return athletes to their previous level of sport with a low risk of recurrence 20 24 25. Ayuob et al 20 have shown in 41 high-level athletes with severe-grade proximal biceps femoris MTJ injuries that 100% return to preinjury level at 13.4±5.1 weeks.…”
Section: Musculotendinous Junction (Mtj) and Intramuscular Tendon Inj...mentioning
confidence: 99%
“… 10 , 11 , 20 , 38 , 40 Less commonly, hamstring injuries involve the distal hamstring muscle complex, and more rarely they include the distal semitendinosus. 26 , 37 …”
mentioning
confidence: 99%